Ecology and Transmission Dynamics of Ostertagia gruehneri in Barrenground Caribou - Hoar, Bryanne (Graduate Studies, 2012)
Climate change in the Arctic is occurring at an accelerated rate and is predicted to alter the ecology of northern ecosystems, including parasite transmission. Barrenground caribou are a keystone species of the tundra and the majority of herds have recently undergone population declines. Ostertagia gruehneri, the most common gastrointestinal parasite of Rangifer tarandus, has been shown to impact the population dynamics of reindeer through decreased food intake, weight loss, and reduced pregnancy rates. Ostertagia gruehneri has a direct life cycle that includes free-living stages. The development and survival rates of this parasite are influenced by climatic factors and its transmission will be affected by climate change. The aim of this research was to investigate how climate change may impact transmission dynamics of O. gruehneri in barrenground caribou. This aim was achieved by developing a more detailed understanding of the life cycle of O. gruehneri and the current transmission patterns within this system. It was expected that the development rate of O. gruehneri would increase and survival rate would decrease with increasing temperatures. Field and laboratory studies, experimental infections of reindeer, and a survey of natural infections in the Bathurst caribou herd were used to study the ecology of O. gruehneri. Results indicate O. gruehneri infective larvae (L3) are available to infect barrenground caribou throughout the first summer, but the migratory behavior of the caribou likely limits exposure risk until the fall. High overwinter survival for both L2 and L3 and nearly 100% larval inhibition may be adaptations to a short growing season and a migratory host, adding important time lags into the system and resulting in a two year transmission pattern. Climate change may increase overall L3 availability by extending the growing season, but increased maximum temperatures are likely to decrease availability midsummer, dividing transmission into spring and fall peaks. Increased development rate and an ...